METHODOLOGY FOR IMPROVING VISUAL ATTENTION AND MOVEMENT COORDINATION THROUGH VOLLEYBALL IN ATHLETES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This study aimed to investigate the effectiveness of volleyball training in improving visual attention and motor coordination among athletes. A total of 60 athletes participated and were divided into control and experimental groups. The experimental group underwent volleyball training three times per week, 90 minutes per session. Visual attention and motor coordination were assessed using specialized tests. Data were analyzed using percentage growth indicators and statistical methods. Volleyball training is an effective pedagogical tool for improving visual attention and motor coordination in athletes. The training enhances psychomotor abilities, concentration, and stress resilience, thereby improving performance in competitions and tournaments.